2013
DOI: 10.1002/pri.1563
|View full text |Cite
|
Sign up to set email alerts
|

Justification for Chest Physiotherapy during Ultra‐Protective Lung Ventilation and Extra‐Corporeal Membrane Oxygenation: A Case Study

Abstract: Regular CPT may have facilitated secretion clearance and lung recovery in this patient. Future research should investigate the optimal CPT techniques for patients with sub-dead space tidal ventilation and extremely low dynamic respiratory compliance during ECMO with ultra-protective ventilatory strategy (UPVS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…The underlying diseases or clinical conditions that led to the indication of ECMO were cystic fibrosis, (11,19,20,23,31-33,36) pulmonary fibrosis, (11,19,20,23,31-33,36) acute respiratory failure, (21,24,25,36) acute respiratory distress syndrome (ARDS), (11,29,33,35) chronic obstructive pulmonary disease, (11) idiopathic pulmonary disease, (11) pulmonary arterial hypertension, (11) usual interstitial pneumonia, (19) acute viral interstitial pneumonia, (28) pneumonia, (19) bridge to lung transplantation (LT), (22,26,34) asthma, (27) lymphangioleiomyomatosis, (23) pleuroparenchymal fibroelastosis, (32) pulmonary embolism, (37) cardiogenic shock, (37) and ventricular dysfunction after cardiac procedure. (37) One study (30) did not report the reason for using ECMO in the sample (n = 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying diseases or clinical conditions that led to the indication of ECMO were cystic fibrosis, (11,19,20,23,31-33,36) pulmonary fibrosis, (11,19,20,23,31-33,36) acute respiratory failure, (21,24,25,36) acute respiratory distress syndrome (ARDS), (11,29,33,35) chronic obstructive pulmonary disease, (11) idiopathic pulmonary disease, (11) pulmonary arterial hypertension, (11) usual interstitial pneumonia, (19) acute viral interstitial pneumonia, (28) pneumonia, (19) bridge to lung transplantation (LT), (22,26,34) asthma, (27) lymphangioleiomyomatosis, (23) pleuroparenchymal fibroelastosis, (32) pulmonary embolism, (37) cardiogenic shock, (37) and ventricular dysfunction after cardiac procedure. (37) One study (30) did not report the reason for using ECMO in the sample (n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…(37) One study (30) did not report the reason for using ECMO in the sample (n = 10). The duration of ECMO support was reported in 12 studies (19,21-23,25,27,29,30,33-36) and ranged from 1 (19) to 125 (35) days.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Fiddler and Williams (2000) emphasized the importance of respiratory therapy when proposed to treat or prevent pulmonary complications in ECMO patients; in-bed positioning and postural exercises are vital components of such treatments, promoting lung ventilation and removal of secretions. Furthermore, it has been found that chest physiotherapy plays an important role in order to facilitate secretion clearance and lung function for a patient while on ECMO (Cork et al, 2014). In a series of candidates awaiting lung transplantation, the post-transplantation duration of ventilation and the postoperative ICU stay were shorter in those undergoing rehabilitation while on ECMO (Thiagarajan et al, 2012).…”
Section: Respiratory Therapymentioning
confidence: 99%
“…Michaels et al 11 used high-frequency percussive ventilation in adult ECMO patients and showed a reduced duration on ECMO. Similarly, Cork et al 12 described the use of various chest physiotherapy and recruitment techniques in adult ECMO patient. Several reports in the pediatric literature have demonstrated the beneficial role of bronchoscopy in the secretion management of pediatric ECMO patients.…”
Section: Discussionmentioning
confidence: 97%